Determination of the Constituent Elements of a Three-Component Hybrid Energy Storage Device for a Plug-In Power Plant for Rolling Stock - Liubarskyi, B. G.; Buriakovskyi, S. G.; Khaustov, O. Yd.; Stetsenko, M. I. (Science and Transport Progress, 2025)
Purpose. The study is aimed at determining the quantitative components of a hybrid three-component energy storage device for a plug-in power plant of rolling stock. Methodology. It was determined that according to the criteria of mass, volume, cost and cost of one kilowatt-hour, none of the options for a single-element storage device simultaneously provides the minimum indicators for all criteria. Thus, it is rational to use a combined three-component energy storage device. An algorithm for setting the problem of conditional minimization of the cost of elements of a three-component combined storage device is considered, which includes the following: 1) setting the objective function in the form of the total cost of the elements; 2) determining the parameters – the number of branches of each type of storage device; 3) setting restrictions on the given energy capacity, power, mass and dimensions and restrictions on the parameters; 4) determining the method for solving the problem, which is the Weyl method. Findings. The authors proved: 1) Analysis of the obtained general results proves the following. With an increase in the specified power, the number of branches of supercapacitors increases and the number of branches of LTO cells decreases. This is due to the fact that supercapacitor cells have the best charge/discharge power indicators, and LTO cells have the best energy-intensive indicators. As for LFP cells, the number of branches ranges from 5 to 24, which provides additional capacity of the storage elements, especially at medium power values; 2) The total capacity component of LTO cells increases with a decrease in the storage power and is 11.5% of the total capacity to 66.4% when the power is reduced from 4,740 kW to 920 kW. The component capacity of supercapacitors, on the contrary, decreases with a decrease in the storage capacity and is 70.6% of the total capacity to 2.4% when the capacity decreases from 4,949 kW to 920 kW, which is due to the expediency of using supercapacitors at high capacities. Originality. The authors of this work have for the first time developed a method for determining the optimal parameters of a combined three-component energy storage based on solving the problem of conditional minimization taking into account mass and dimensional constraints. Practical value. Based on the results obtained, it is possible to determine the parameters of combined storage for rolling stock using the example of plug-in hybrid power plants of rail rolling stock of a quarry locomotive.